Let x[n] = u[n] – u[n – 7] and h[n] = {(1/2)^n 0 lessthanorequalto n lessthanorequalto 3 0 otherwise. (a) Plot x[n]. Plot h[n]. Label the amplitudes for each sample. (b) If we now assume x[n] = delta [n] + delta [n – 1] + delta [n – 2] and y[n] = x[n] * h[n], where h[n] is as defined above, plot y[n] on the axis below.

96 3 - Let x[n] = u[n] - u[n - 7] and h[n] = {(1/2)^n 0 lessthanorequalto n lessthanorequalto 3 0 otherwise. (a) Plot x[n]. Plot h[n]. Label the amplitudes for each sample. (b) If we now assume x[n] = delta [n] + delta [n - 1] + delta [n - 2] and y[n] = x[n] * h[n], where h[n] is as defined above, plot y[n] on the axis below.

This content is for Premium members only.
sign up for premium and access unlimited solutions for a month at just 5$(not renewed automatically)


images - Let x[n] = u[n] - u[n - 7] and h[n] = {(1/2)^n 0 lessthanorequalto n lessthanorequalto 3 0 otherwise. (a) Plot x[n]. Plot h[n]. Label the amplitudes for each sample. (b) If we now assume x[n] = delta [n] + delta [n - 1] + delta [n - 2] and y[n] = x[n] * h[n], where h[n] is as defined above, plot y[n] on the axis below.

already a member please login